Variações de indicadores de adiposidade e sua relação com distúrbios cardiometabólicos em população rural - Tatiane Gea Horta (2009)
Obesity is worldwide recognized as an important public health matter and it is associated tometabolic and hemodynamic disorders. Evidences have shown waist circumference (WC) as abetter predictor of dyslipidemia and cardiovascular risk, while others believe that BMI as themajor factor for developing these disorders. The objective was to evaluate associationsbetween changes of anthropometric indicators with dyslipidemia and blood pressure values ina rural population of Brazil. Population based study in a rural community followed 207individuals aged between 18 and 75 years-old (101 women and 106 men) across 4 years.Demographic, lifestyle, anthropometric, biochemical and hemodynamic characteristics wasassessed in 2004 and 2008. Multivariate linear regression was used to evaluate the effect ofBMI and WC changes (2004-2008) over serum lipids and blood pressure levels. Mean agewas 44 years-old. Overweight and obesity prevalences were 22.2% and 6.8%, respectively, in2008. Thirty-eight percent of the total population was classified as hypertensive objects. Meanvalues for BMI and WC were increased, overweight and obesity were significantly higheramong women. Mean of weight gain along the study was 1,7 kg, BMI increased in general0.72 kg/m2 and WC, 2.15 cm. BMI and WC changes were directly associated to systolic anddiastolic blood pressure. Age and BMI changes were associated to total cholesterol, LDLcholesterol and LDL/HDL ratio. No significant association was found with HDL cholesterol.The rural population studied shown obesity as an important public health matter. BMIchanges were shown as an independent predictor for metabolic disorders and for increaseddiastolic blood pressure, while changes in WC were an independent predictor for systolicblood pressure. Changes of both obesity indexes BMI and WC in four years were presented aspotencial effects on cardiometabolic disturbances.